2005
DOI: 10.1007/s11177-005-0208-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Genetic Diversity of Spring Durum Wheat (Triticum durum Desf.) Cultivars Released in Russia in 1929–2004

Abstract: Based on genealogical analysis, the genetic diversity of 78 spring durum wheat cultivars released in Russia in have been examined. The temporal trends of change in diversity were studied using series of n × m matrices (where n is the number of the cultivars and m is the number of original ancestors) and calculating coefficients of parentage in sets of cultivars released in particular years. The pool of original ancestors of spring durum wheat cultivars includes 90 landraces and old varieties, more than a half… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Indirect approaches to measure change in genetic diversity have also been employed, including coefficients of parentage and related metrics used to compare pedigrees (e.g. Bowman et al ., 2003; Martynov et al ., 2005, 2006). Within‐variety diversity research has also included investigations of changes in phenotypic variation, often focusing on agronomic traits (e.g.…”
Section: Defining and Measuring Crop Genetic Erosionmentioning
confidence: 99%
“…Indirect approaches to measure change in genetic diversity have also been employed, including coefficients of parentage and related metrics used to compare pedigrees (e.g. Bowman et al ., 2003; Martynov et al ., 2005, 2006). Within‐variety diversity research has also included investigations of changes in phenotypic variation, often focusing on agronomic traits (e.g.…”
Section: Defining and Measuring Crop Genetic Erosionmentioning
confidence: 99%
“…Pedigree studies have been used in an attempt to overcome some of the problems in assessing diversity based on varieties. Using information on ancestors, these studies estimated the distinctness of cultivars and the extent to which old landraces are present in the pedigree of modern cultivars (Souza and Sorrells, 1989; Dobrotvorskaya et al , 2004; Martynov et al , 2005; Martynov et al , 2006). The calculated diversity indices of groups of cultivars are based on the frequencies of the original ancestors in the pedigrees.…”
Section: Analysis Of Genetic Erosion At Different Levels Of Integrationmentioning
confidence: 99%
“…A large proportion of the local landraces disappeared from the pedigree of the released cultivars, but these were replaced by foreign material resulting in maintenance of diversity levels. The loss of local landraces from the pedigrees is viewed by the authors as evidence of genetic erosion (Dobrotvorskaya et al , 2004; Martynov et al , 2005, 2006). However, as local diversity levels were maintained, the results did not point towards genetic erosion at a regional level, while a conclusion about genetic erosion at a global level can only be made if it can be demonstrated that this lost material harboured unique characters that are not present in other areas or varieties.…”
Section: Analysis Of Genetic Erosion At Different Levels Of Integrationmentioning
confidence: 99%
“…Studies on the effect of modern plant breeding on genetic diversity in wheat have shown no loss of allele numbers or genetic diversity over time (Donini et al, 2000; Martynov et al, 2005; Huang et al, 2007). Donini et al (2000) determined that the breeding process fixed alleles at agronomically important loci in UK wheat, but it did not significantly affect allele frequency at loci not affected by selection.…”
mentioning
confidence: 99%